Risk assessment of new sequencing information for genetically modified soybean A2704‐12 - European Food Safety Authority (EFSA); Silvia Federici; Konstantinos Paraskevopoulos (EFSA Journal, 2018)
Abstract The GMO Panel has previously assessed genetically modified (GM) soybean A2704‐12. This soybean was found to be as safe and nutritious as its conventional counterpart with respect to potential effects on human and animal health and the environment in the context of its intended uses. On 5 June 2018, the European Commission requested EFSA to analyse new nucleic acid sequencing data and updated bioinformatics data for GM soybean A2704‐12 and to indicate whether the previous conclusions of the GMO Panel on the risk assessment of GM soybean A2704‐12 remain valid. The new sequencing data indicated seven nucleotide differences as compared to the sequence originally provided in application EFSA‐GMO‐NL‐2005‐18; six nucleotides in the 3′ genomic flanking region and one nucleotide in the soybean chloroplast DNA fragment located 5′ to the insert. Another nucleotide located in a polylinker region of the insert reported as ambiguous in the originally submitted sequence was resolved in the new sequence data. Based on the information provided on the locations affected by the reported nucleotide differences, no open reading frames (ORFs) spanning the junction site between the insert and the 3′ genomic flanking DNA are affected by the differences in the 3′ genomic flanking region and were therefore excluded from the assessment. However, one ORF spanning the junction between the 5′‐chloroplast DNA fragment and the insert and six ORFs overlapping with the resolved nucleotide in the polylinker region were affected and therefore assessed. Based on the analysis of the provided data, EFSA considers that it is highly unlikely that the reported sequence differences (including the single nucleotide difference in the 5′‐chloroplast DNA fragment) are due to spontaneous mutations and can therefore most likely be attributed to sequencing errors in the originally reported soybean A2704‐12 event sequence. With the exception of bioinformatic analyses, the studies performed for the risk assessment of soybean A2704‐12 are not affected. The new sequencing data and the bioinformatic analyses performed on the new sequence did not give rise to safety issues. Therefore, EFSA concludes that the original risk assessment of soybean A2704‐12 remains valid.